Comparison of complications and prolapse recurrence between laparoscopic and vaginal uterosacral ligament suspension for the treatment of vaginal prolapse. Issue 5 (May 2016) - Turner, Lindsay; Lavelle, Erin; Shepherd, Jonathan
Abstract Introduction and hypothesis Our objective was to compare complications and prolapse recurrence between laparoscopic (L-USLS) and vaginal (V-USLS) uterosacral ligament suspensions. Methods This is a retrospective study of USLS procedures performed at a large academic center from 2011 to 2014. Patient demographics, surgical data, complications, and prolapse recurrence of L-USLS and V-USLS were compared. Logistic regression identified predictors of operative time, complications, and prolapse recurrence. Results There were 54 L-USLS and 119 V-USLS procedures with median follow-up of 21.5 weeks (IQR 9.3–50.8). Women undergoing L-USLS were less likely to have medical comorbidities and had less severe prolapse, but were more likely to report prior hysterectomy. L-USLS had longer operative times (190.1 ± 46.8 vs 172.7 ± 47.3 min, p  = 0.03), but after correcting for concomitant procedures, the operative times of the two approaches were not significantly different (adjusted OR 1.00, 95%CI 0.99–1.00). There was no significant difference in complications between groups (24.1 % vs 21.8 %, p  = 0.75). However, there were nonsignificant trends toward more ureteral injuries and suture removals following V-USLS. Postoperative POP-Q points of the groups did not differ, except for total vaginal length (TVL), which was longer after L-USLS (8.3 ± 1.1 cm vs 7.4 ± 1.2 cm, p  < 0.001). 19 patients met the composite definition of prolapse recurrence, with no significant difference between groups (16.2 % vs 16 %, p  = 0.98). After adjusting for preoperative prolapse stage, route was not a significant predictor of prolapse recurrence (adjusted OR 0.39, 95 % CI 0.12–1.30). Conclusions L-USLS has comparable clinical outcomes, with similar rates of complications and prolapse recurrence to the traditional vaginal approach.